1990
DOI: 10.1038/bjc.1990.162
|View full text |Cite
|
Sign up to set email alerts
|

The effects of three bioreductive drugs (mitomycin C, RSU-1069 and SR4233) on cell lines selected for their sensitivity to mitomycin C or ionising radiation

Abstract: Summary We have investigated the cross-sensitivity of a number of cell lines to three different classes of bioreductive drugs under both aerobic and hypoxic conditions. The cell lines used were selected for their sensitivity to DNA-damaging agents and fall into two groups. One group, MMC cells derived from CHO-KI cells (Robson et al., 1985), show a range of sensitivities to mitomycin C in air. The second group, irs cells were cloned from V79 Chinese hamster fibroblasts (Jones et al., 1987) and exhibit sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
9
0

Year Published

1991
1991
1997
1997

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…This may be related to the fact that AT cells have not shown a gross defect in DNA double strand break rejoining, although they do show reduced rejoining of chromosome breaks compared to normal cells (Cornforth & Bedford, 1985), and lack the ability to repair poterftially lethal damage as judged by delayed plating experiments (Biedermann & Brown, 1989). This lack of correlation between X-ray and SR4233 sensitivity is also seen in the data of Keohane et al (1990). These investigators showed that irs cells, which are radiationsensitive, but not deficient in the repair of DNA double strand breaks (Jones et al, 1990), display similar hypoxic cytotoxicities by SR 4233 to the parental V79 vells.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…This may be related to the fact that AT cells have not shown a gross defect in DNA double strand break rejoining, although they do show reduced rejoining of chromosome breaks compared to normal cells (Cornforth & Bedford, 1985), and lack the ability to repair poterftially lethal damage as judged by delayed plating experiments (Biedermann & Brown, 1989). This lack of correlation between X-ray and SR4233 sensitivity is also seen in the data of Keohane et al (1990). These investigators showed that irs cells, which are radiationsensitive, but not deficient in the repair of DNA double strand breaks (Jones et al, 1990), display similar hypoxic cytotoxicities by SR 4233 to the parental V79 vells.…”
Section: Discussionmentioning
confidence: 49%
“…We have proposed that SR 4233 is reduced via a single-electron reduction pathway to form a free radical intermediate, the structure of which has been recently confirmed by ESR (Lloyd & Mason, personal communication). Under aerobic conditions, the radical reacts with oxygen in a futile one-electron reduction cycle, generating superoxide in the process (Laderoute et al, 1988). In the absence of oxygen, the SR 4233 radical may abstract hydrogen from DNA and other macromolecules, forming strand breaks which ultimately result in cell death.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the variability in differential hypoxic cytotoxicity for different cell lines shown for SR4233, values obtained from different investigators are consistently higher than those obtained for the quinone antibiotic mitomycin C, for which values of only 1 to 5 are found (Fracasso & Sartorelli, 1986;Keohane et al, 1990;Stratford & Stephens, 1989), and for the 2-nitroimidazole misonidazole for which values of five to 15 are typical (Stratford & Stephens, 1989;Taylor & Rauth, 1978). However, comparable high values are often, though not universally, reported for the dual function nitroimidazole, RSU 1069 (Adams et al, 1992;Roizin-Towle et al, 1990;Stratford & Stephens, 1989).…”
mentioning
confidence: 94%
“…Second, the nitroimidazoles, although developed as radiation sensitisers, show preferential toxicity to hypoxic cells which is high in the case of the dual function agent, RSU 1069 (Stratford & Stephens, 1989;Stratford et al, 1986). The third class of bioreductive cytotoxic drugs are the benzotriazine di-N-oxides of which SR 4233 (3-amino-1,2,4-benzotriazine 1,4-dioxide, WIN 59075, tirapazamine) is the prototype compound (Zeman et al, 1986 (Adams et al, 1992;Costa et al, 1989;Stratford & Stephens, 1989), although it has also been reported that certain cell lines with repair deficiencies have somewhat lower differential cytotoxicities (Keohane et al, 1990).…”
mentioning
confidence: 99%